Propostas metodológicas para a educação ambiental: representação social e interpretação de imagens - Silveira, Anamaria (Universidade Federal de São Carlos, 2003)
This paper had the objective of applying a methodology which is aimed at the Public School, more specifically to Fundamental Education, as a contribution to the implementation of Environmental Education programs. The target public for this study were fifth grades students attending the state public school Antônio Militão de Lima and their respective teachers. In order to achieve the proposed objectives, a pedagogical intervention which privileged the Theory of Social Representation was established, based on the methodology developed by the educator Marcos Reigota and an interdisciplinary program, whose aim was to arouse the elements involved towards the forming of citizenship and ecological awareness. The teachers were oriented to the importance of collective and interdisciplinary involvement through offering capacitating courses and interaction with local reality. The results obtained demonstrated the true difficulties faced today by the Public Scholl, and their development of program allowed us to conclude that: 1) capacitating courses for teachers could contribute to arousing a mere critical vision of reality in the educator; 2) the results brought a series of information (informal) through interviews as well as through classroom discussions regarding the children s learning. The Theory of Social Representation and methodology of image interpretation were efficient to motivation students, teachers and other involved.
Keywords: Educação ambiental; Bacia hidrográfica; São Carlos (SP); Representação social; CIENCIAS BIOLOGICAS::ECOLOGIA